2019
DOI: 10.1155/2019/7981687
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors and Oral Health-Related Behaviours Associated with Dental Caries in Preschool Children from Central Italy (Province of Ascoli Piceno)

Abstract: Background. Dental caries is a serious oral health concern with high prevalence in preschool children. Aim. To assess the association among oral health-related behaviors, socioeconomic factors, and dental caries in Italian preschool children. Design. 513 preschool children from 3 to 6 years of age, enrolled in nursery schools in central Italy, represent the population of the present study. The children underwent dental clinical examination and were divided on the basis of their caries experience in the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Recently, a systematic review underlined that a proper education about dental procedure was demonstrated to have a role in the control of pain and anxiety generally associated with dental procedure. [32] The impact of the socio-economic level on oral health has been recently investigated and shown to have an effect mostly for pre-school children, for which the level of education of the parents can play a role [10], and also for the interceptive diagnosis of the dental problems to prevent, such as caries or malocclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a systematic review underlined that a proper education about dental procedure was demonstrated to have a role in the control of pain and anxiety generally associated with dental procedure. [32] The impact of the socio-economic level on oral health has been recently investigated and shown to have an effect mostly for pre-school children, for which the level of education of the parents can play a role [10], and also for the interceptive diagnosis of the dental problems to prevent, such as caries or malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that factors such as age, race, gender, oral hygiene habits, socio-economical status, and oral hygiene education can define the state of oral hygiene, and improving the knowledge on oral hygiene can bring to a greater awareness, especially regarding children and adolescents [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of caries in European children seems therefore to assess at over 30% (20 to 90% according to the European Regional Office of WHO [ 27 ]. A trend towards decreasing caries prevalence in school children has been described in several studies, nevertheless some authors have observed a plateau in the decline of caries prevalence in pre-schoolers in the recent years, especially in immigrant children or children from a low socio-economic level [ 19 , 27 ]. A limitation of our study consists in the fact that no oral examination was performed on the children and therefore the answers concerning disease prevalence could not be clinically confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The present project was organized in the following way. Firstly, a questionnaire about lifestyles, eating habits and oral hygiene was prepared by a group of expert dentists on the basis of potential variables observed after a summary of the previous literature [16][17][18][19][20][21]. The quantitative content validity of the questionnaire was obtained using Waltz and Bausell's method.…”
Section: Methodsmentioning
confidence: 99%